Age-induced nitrative stress decreases retrograde transport of proNGF via TrkA and increases proNGF retrograde transport and neurodegeneration via p75NTR - Kropf, Erika; Shekari, Arman; Jaberi, Sama; Puri, Anish; Wu, Chengbiao; Fahnestock, Margaret (Frontiers in Molecular Neuroscience, 2023)
Introduction Axonal transport of pro nerve growth factor (proNGF) is impaired in aged basal forebrain cholinergic neurons (BFCNs), which is associated with their degeneration. ProNGF is neurotrophic in the presence of its receptor tropomyosin-related kinase A (TrkA) but induces apoptosis via the pan-neurotrophin receptor (p75NTR) when TrkA is absent. It is well established that TrkA is lost while p75NTR is maintained in aged BFCNs, but whether aging differentially affects transport of proNGF via each receptor is unknown. Nitrative stress increases during aging, but whether age-induced nitrative stress differentially affects proNGF transport via TrkA versus p75NTR has not yet been studied. Answering these questions is essential for developing an accurate understanding of the mechanisms contributing to age-induced loss of proNGF transport and BFCN degeneration. Methods In this study, fluorescence microscopy was used to analyze axonal transport of quantum dot labeled proNGF in rat BFCNs in vitro. Receptor specific effects were studied with proNGF mutants that selectively bind to either TrkA (proNGF-KKE) or p75NTR (proNGF-Δ9-13). Signaling factor activity was quantified via immunostaining. Results Young BFCNs transported proNGF-KKE but not proNGF-Δ9-13, and proNGF transport was not different in p75NTR knockout BFCNs compared to wildtype BFCNs. These results indicate that young BFCNs transport proNGF via TrkA. In vitro aging increased transport of proNGF-Δ9-13 but decreased transport of proNGF-KKE. Treatment with the nitric oxide synthase inhibitor L-NAME reduced retrograde transport of proNGF-Δ9-13 in aged BFCNs while increasing retrograde transport of proNGF-KKE but did not affect TrkA or p75NTR levels. ProNGF-Δ9-13 induced greater pro-apoptotic signaling and neurodegeneration and less pro-survival signaling relative to proNGF-KKE. Discussion Together, these results indicate that age-induced nitrative stress decreases proNGF transport via TrkA while increasing proNGF transport via p75NTR. These transport deficits are associated with decreased survival signaling, increased apoptotic signaling, and neurodegeneration. Our findings elucidate the receptor specificity of age-and nitrative stress-induced proNGF transport deficits. These results may help to rescue the neurotrophic signaling of proNGF in aging to reduce age-induced loss of BFCN function and cognitive decline.